Perception and Participation of Masbagek Community In Martial Arts Tradition Spend - Anam, Khaerul; Wahidah, Ananda; Saputra, Anggun Anggita; Arofah, Zianul; Ramadhania, Aini (CV. Publikasi Indonesia, 2024)
The Belaniakan tradition is an ancient Sasak culture that until the time of Tetan was preserved by the Masbagek community. This research aims to determine the perception and participation of the Masbagek community in the bukakkan martial arts tradition. This research uses a qualitative approach with ethnographic methods. The informant selection technique is purposive sampling technique. The results of the research show that the Masbagek community's perception of the shopping tradition is positive towards the shopping tradition. Forms of community participation in organizing this shopping tradition include: as organizers, organizers and participants